Malignant pleural effusions: Are we better than the past? - Karcıoğlu, Oğuz; Tekin, Fatih; Öztürk, Ebru; Önder, Sevgen; Selçuk, Ziya Toros (Acta Medica, 2024)
Objective: Malignant pleural effusion (MPE) is indicative of advanced-stage disease and a poor prognosis in almost all cancer types. Lung and breast cancers are the predominant malignancies causing MPE, collectively representing over 60% of the total. In recent years, cancer has become a type of chronic disease, with advancements in diagnostic tools and treatment strategies. Our objective was to assess the evolution of primary diagnoses, survival rates, and associated variables among individuals with MPE in recent years. Materials and Methods: A retrospective search was conducted on the demographics, comorbidities, primary cancer sites, diagnostic interventions, and laboratory results of patients diagnosed with MPE between January 1, 2005, and July 30, 2018. Results: Of the 663 patients who have MPE, the female/male ratio was 373/290. The mean age was 59.2 ± 14.0 at the time of diagnosis. The most common cancers were lung cancer (30.9%), breast cancer (23.3%), and gastrointestinal system cancers (16.62%). It was observed that the rate of MPE due to lung cancer increased gradually over the years. Initially, breast cancer constituted the most prevalent diagnosis in 28.2% of cases, whereas lung cancer rose to the top as the most prevalent in the second and third five-year periods (28.9% and 37.4%, respectively). Overall, the median survival time was 2.07 months. Kaplan-Meier analysis also revealed that survival times did not change significantly over fourteen years. Conclusion: Advances in diagnostic methods and treatment modalities have altered the most common primary cancer causing MPE in recent years but have not contributed to survival time.